Clinical Observation on Chronic Low Back Pain Treated by Sling and Tuina Exercise Therapy - Ning WANG; Yi DING; Qiangqiang XU; Jiapeng ZHANG; LI Li (康复学报)
Objective:To observe the changes of morphology of local core stable muscles including transversus abdominal muscle and multifidus muscle by using musculoskeletal ultrasound, and explore the clinical effect of sling and tuina exercise technique on chronic low back pain (CLBP).Methods:A total of 90 CLBP cases were collected according to the random number table method, which were outpatient and inpatient admitted to the rehabilitation department of the Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine. The eligible patients were assigned to the sling and tuina exercise technique group, the sling exercise therapy group and the tuina group, and 30 cases in each group. The sling exercise therapy group received active sports training under limb suspension with sling in the lateral position, the prone position and the supine position. The tuina treatment group was given pressing, rubbing, plucking and other manipulations to increase pain areas in lumbar muscles, improve lumbar blood circulation and relieve muscle tension and spasm. The sling and tuina exercise technique group received sling exercise combined with tuina. All treatment lasted for four weeks, once a day, 30 minutes each time, five times a week. The changes of thickness of transversus abdominal muscle and multifidus muscle were detected by using musculoskeletal ultrasound, the patient's pain improvement was assessed by the visual analogue scale (VAS), the improvement of dysfunction was assessed by the Oswestry dysfunction index (ODI), and the patient's persistent sitting condition was assessed by the continuous sitting time before treatment and four weeks after treatment respectively. The improvement of pain and dysfunction were assessed by VAS and ODI one month and two months after the end of treatment.Results:There were no significant differences among the three groups in VAS score, ODI score, duration of standing and muscle thickness before the treatment (P> 0.05). After four weeks of treatment, the thickness of transversus abdominal muscle and multifidus muscle in the three groups were increased, the VAS score and ODI score were decreased, and the continuous sitting time was prolonged compared with that before the treatment (P< 0.05). After four weeks of treatment, the thickness of affected transversus abdominal muscle and multifidus muscle in the sling and tuina exercise therapy group was higher than other two groups, the VAS score and ODI score was lower than other two groups, the continuous sitting time was prolonged compared with other two groups, and the difference was statistically significant (P< 0.05). Compared with before treatment, the VAS score and ODI score were decreased significantly one month and two months after the end of treatment (P< 0.05), but there was no difference between four weeks after treatment and one month or two months after the whole treatment (P> 0.05); the VAS score and ODI score in the sling and tuina exercise therapy group was lower than other two groups one month and two months after the end of treatment (P< 0.05).Conclusion:Sling and tuina exercise therapy can increase the muscle thickness of affected transversus abdominal muscle and multifidus muscle in patients with chronic low back pain, and effectively alleviate the pain problem of patients with chronic low back pain and improve the lumbar muscles dysfunction of patients. The method is worthy of clinical promotion, and continuous training should be insist to ensure efficacy.